Al compás del fin del mundo: La Virgen de los sicarios de Fernando Vallejo (Altre Modernità, 2013)
The novel La Virgen de los sicarios (Our Lady of the Assassins) (1994) by Fernando Vallejo offers a terrifying vision of the apocalyptic and cultural transformations that took place in Colombia from receipt of the globalizing economic policies of the late nineteenth century. This is how a communication model circulated, based mainly on the acoustics which promoted interference and disruption in intersubjective relations, generating destruction and violence. The countless allusions to John’s Book of Revelation in the novel gives a prophetic and eschatological sense to the acoustic signs of an unfinished and devastating modernity which plagued Colombia at the end of last century, with no possibility of salvation. Vallejo's novel attributes this apocalyptic sense the "revelation" of an essential truth of the world and the people of Latin America, the crude unveiling of something hidden and secret, that is, the incorporeal effects of acoustic devices which, consciously or unconsciously, trigger and feed violence in Colombia.